KONSTRUKSI BERPIKIR QIYAS SEBAGAI PENALARAN IJTIHAD DALAM INSTINBATH HUKUM EKONOMI DAN KEUANGAN SYARIAH - Hidayatullah, Muhammad Syarif (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2020)
The development of a dynamic era produces many new products and cases that are present in the modern economy. Islamic law has set and provided restrictions on these issues concerning aspects of halal and haram. The Qiyas method is needed in legal studies to produce fiqh formulations in Islamic economic and financial law. This paper aims to explain the concept of qiyas as a method of istinbath Islamic law and then examine the application of qiyas in the discovery of Islamic economic and financial law. This type of research is normative legal research with a conceptual approach. Legal material is collected through the study of literature with discussion of ushûl fiqh (Islamic law methodology) dan fiqh mu’âmalah (Islamic Jurisprudence about economics and finance) in classical and contemporary literature. The existence of qiyas as a method of istinbath law has a very important position in economics and finance. New products and cases that are present need to be responded and analyzed. Exploring the law with qiyas must be done throught careful and in-depth studies by looking at the similarity of true ‘illat (legal motives) so that the construction process of thinking qiyas in legal discovery can be applied appropriately.